(untitled) (Colombia Medica, 2014)
Introduction: Urinary tract infection (UTI) is one of the most common bacterial infections in childhood and causes acute and chronic morbidity and long-term hypertension and chronic kidney disease. Objectives: To describe the demographic characteristics, infectious agents, patterns of antibiotic resistance, etiologic agent and profile of susceptibility and response to empirical treatment of UTI in a pediatric population. Methods: This is a descriptive, retrospective study. Results: Included in the study were 144 patients, 1:2.06 male to female ratio. The most common symptom was fever (79.9%) and 31.3% had a history of previous UTI. 72.0% of the patients had positive urine leukocyte count (>5 per field), urine gram was positive in 85.0% of samples and gram negative bacilli accounted for 77.8% for the total pathogens isolated. The most frequent uropathogens isolated were Escherichia coli and Klebsiella pneumoniae. Our E.coli isolates had a susceptibility rate higher than 90% to most of the antibiotics used, but a resistance rate of 42.6% to TMP SMX and 45.5% to ampicillin sulbactam. 6.3% of E. coliwas extended-spectrum beta-lactamases producer strains. The most frequent empirical antibiotic used was amikacin, which was used in 66.0% of the patients. 17 of 90 patients who underwent voiding cistouretrography (VCUG) had vesicoureteral reflux. Conclusion: This study revealed that E. coli was the most frequent pathogen of community acquired UTI. We found that E. coli and other uropathogens had a high resistance rate against TMP SMX and ampicillin sulbactam. In order to ensure a successful empirical treatment, protocols should be based on local epidemiology and susceptibility rates.